Raw materials for glass and ceramics : - Sinton, Christopher W. (Wiley, 2006)
Raw Materials for Glass and Ceramics presents all classes of materials, the roles they play, their sources and extraction processes, and quality control issues and regulations impacting the industry, as well as: * A thorough description of the formation and evaluation of raw material deposits and location of the important sources * Complete analysis of all the raw materials used in the ceramic and glass industries, including natural, processed, recycled, and synthetic materials * An explanation of the raw materials industry, including transportation, environmental and health concerns, and quality specifications